Heparin-Poloxamer Thermosensitive Hydrogel Loaded with bFGF and NGF Enhances Peripheral Nerve Regeneration in Diabetic Rats. (June 2018) - Li, Rui; Li, Yiyang; Wu, Yanqing; Zhao, Yingzheng; Chen, Huanwen; Yuan, Yuan; Xu, Ke; Zhang, Hongyu; Lu, Yingfeng; Wang, Jian; Li, Xiaokun; Jia, Xiaofeng; et al.
Abstract: Peripheral nerve injury (PNI) is a major burden to society with limited therapeutic options, and novel biomaterials have great potential for shifting the current paradigm of treatment. With a rising prevalence of chronic illnesses such as diabetes mellitus (DM), treatment of PNI is further complicated, and only few studies have proposed therapies suitable for peripheral nerve regeneration in DM. To provide a supportive environment to restore structure and/or function of nerves in DM, we developed a novel thermo-sensitive heparin-poloxamer (HP) hydrogel co-delivered with basic fibroblast growth factor (bFGF) and nerve growth factor (NGF) in diabetic rats with sciatic nerve crush injury. The delivery vehicle not only had a good affinity for large amounts of growth factors (GFs), but also controlled their release in a steady fashion, preventing degradation in vitro. In vivo, compared with HP hydrogel alone or direct GFs administration, GFs-HP hydrogel treatment is more effective at facilitating Schwann cell (SC) proliferation, leading to an increased expression of nerve associated structural proteins, enhanced axonal regeneration and remyelination, and improved recovery of motor function (all p < 0.05). Our mechanistic investigation also revealed that these neuroprotective and neuroregenerative effects of the GFs-HP hydrogel may be associated with activations of phosphatidylinositol 3 kinase and protein kinase B (PI3K/Akt), janus kinase/signal transducer and activator of transcription 3 (JAK/STAT3), and mitogen-activated protein kinase kinase/extracellular signal-regulated kinase (MAPK/ERK) signaling pathways. Our work provides a promising therapy option for peripheral nerve regeneration in patients with DM.